Performance analysis of 60 GHz pulse multiuser communication system based on cross-layer strategy - Xuehua LI; Chen SHEN; Yuanyuan YAO (Dianxin kexue)
Due to the advantages of license-free,strong directionality,high system capacity,and high transmission rate of Gbit/s,60 GHz band is listed as one of the candidate bands for new radios (new radio).In 5G ultra-dense networking scenario,the randomness of node switching caused by the decrease of the distance between network nodes may cause severe multiple access interference and resource mismatch problems.In this regard,based on the concept of cross-layer collaborative design,a resource scheduling strategy based on fairness was proposed.The multiple access performance of the strategy was simulated in a 60 GHz pulsed wireless communication system based on TH-PAM (time hopping pulse amplitude modulation).Simulation results show that compared with the system with pure physical layer optimization algorithm,the multiple access system which adopts this strategy shows stronger fairness and lower system error rate,but it needs increase the transmission power to meet the requirements of the coverage of the equivalent communication system.That is,there is a certain trade-off between the energy and fairness of the system,which can be used to guide the structure and deployment of the actual communication system.